Teaching about evolution and the nature of science - National Academy of Sciences (U.S.). Working Group on Teaching Evolution (Washington, DC : National Academy Press, 1998)
"Teaching About Evolution and the Nature of Science provides a well-structured framework for understanding and teaching evolution. Written for teachers, parents, and community officials as well as for scientists and educators, this book illustrates how evolution explains both the great diversity and the underlying similarity of the earth's organisms; it explores how scientists approach the question of evolution; and it describes the nature of science as a way of knowing about the natural world. In addition, the book provides answers to frequently asked questions to help readers understand many of the issues and misconceptions about evolution."--Jacket.
Why teach evolution? -- Major themes in evolution -- Evolution and the nature of science -- Evolution and the National Science Education Standards -- Frequently asked questions about evolution and the nature of science -- Activities for teaching about evolution and the nature of science -- Selecting instructional materials.
Includes bibliographical references (pages 130-132) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Evolution (Biology) -- Study and teaching; Science -- Study and teaching; Évolution (Biologie) -- Étude et enseignement; Sciences -- Étude et enseignement; SCIENCE -- Life Sciences -- Evolution; Evolution (Biology) -- Study and teaching; Science -- Study and teaching; Evolution (Biology) -- Study and teaching; Science -- Study and teaching; Evolutietheorie; Onderwijsprogramma's.; Vrijheid van onderwijs; Évolution (biologie) -- Étude et enseignement; Sciences -- Étude et enseignement; Electronic publications; Electronic book